PERANCANGAN SISTEM INFORMASI PENDATAAN WARGA PADA KELURAHAN KEBAYORAN LAMA – JAKARTA SELATAN - Agung Priambodo; Saeful Anwar (FAKULTAS TEKNIK, 2021)
Utilization of information systems is very useful in all fields, including in the Kebayoran Lama sub-district where there are still problems, especially in terms of collecting data and searching for citizen data which is quite ineffective and efficient. This is because the old Kebayoralan kelurahan office still does not have a system for collecting data on its citizens. Therefore, the purpose of this study is to design an information system for collecting data on residents in the Kebayoran Lama village, and in this case the author uses the waterfall system design method and before implementing the system that has been built, testing is carried out first using the black box method and the results of the research. What has been made is that the Kebayoran Lama kelurahan is now more effective and efficient as well as a useful means of accessing information on citizen data collection and can more easily provide complete information on citizen data collection.